1989
DOI: 10.1016/0736-5748(89)90031-2
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase in the development of chick dorsal root ganglia

Abstract: Acetylcholinesterase is expressed in chick dorsal root ganglia neurons very early in development. Since the physiological role of the enzyme in these cells is still obscure, it appeared of interest to investigate its modifications in the course of development. The specific activity of acetylcholinesterase in chick dorsal root ganglia increases, during in ovo development, from day E5 to day E13; after day E13 there is a decrease. Conversely, when acetylcholinesterase activity was expressed on a per ganglion bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 22 publications
4
24
0
Order By: Relevance
“…In the avian embryo, Layer and colleagues (Layer, 1990(Layer, , 1991Layer and Kaulich, 1991) have shown a transient AChE expression in developing spinal cord neurons that progresses in a rostrocaudal wave, coinciding with periods of axonal outgrowth (Weikert et al, 1990). Temporary AChE expression has also been documented in developing dorsal root ganglion (DRG) neurons (Cochard and Coltey, 1983;Moody and Stein, 1988;Biagioni et al, 1989;Layer and Kaulich, 1991;Koenigsberger et al, 1998) and, later, in their axons and growth cones in the spinal cord (Tennyson and Brzin, 1970;Oudega and Marani, 1990).…”
Section: Introductionmentioning
confidence: 94%
“…In the avian embryo, Layer and colleagues (Layer, 1990(Layer, , 1991Layer and Kaulich, 1991) have shown a transient AChE expression in developing spinal cord neurons that progresses in a rostrocaudal wave, coinciding with periods of axonal outgrowth (Weikert et al, 1990). Temporary AChE expression has also been documented in developing dorsal root ganglion (DRG) neurons (Cochard and Coltey, 1983;Moody and Stein, 1988;Biagioni et al, 1989;Layer and Kaulich, 1991;Koenigsberger et al, 1998) and, later, in their axons and growth cones in the spinal cord (Tennyson and Brzin, 1970;Oudega and Marani, 1990).…”
Section: Introductionmentioning
confidence: 94%
“…Based on these observations, it has been proposed that AChE may have a novel, non-cholinergic role in morphogenetic movements and path-finding during development of the nervous system (Robertson, 1987;Hutchins and Casagrande, 1988;Kristt, 1989;Layer et al, 1988;Weikert et al, 1990). In this regard, we have demonstrated that inhibition of AChE activity retards neuritic outgrowth from cultured dorsal root ganglia neurons (DRGN), which express AChE activity, yet they are neither cholinergic nor cholinoceptive (Bigbee and Foster, 1989;Biagioni et al, 1989).To explore the possible interaction between AChE activity and environment we have studied the effect of substrata, with variable degrees of permissiveness to neuritic outgrowth, on the levels of AChE activity in Received March 28, 1991; revised June 18, 1991 …”
mentioning
confidence: 93%
“…Address correspondence to J. W. Bigbee axonal outgrowth from these cells (1,8,9). In the peripheral nervous system (PNS), AChE is transiently expressed by developing dorsal root ganglion (DRG) neurons (10)(11)(12)(13)(14) and later in their axons and growth cones in the spinal cord (15,16 (18). BW284c51 is a bis-quaternary nitrogen compound that is a highly specific inhibitor for AChE.…”
mentioning
confidence: 99%